Empirical development and verification of career well-being scale for teachers in Taiwan: Implications for workplace counseling - Yu, Min-Ning; Yang, Peter (Frontiers in Psychology, 2022)
As it is one decade since the establishment of Kidd’s (2008) model, an analysis of the career well-being (CWB) experienced by Eastern workers is both timely and necessary. To this end, we conducted a series of logical investigations of CWB in Taiwanese school teachers. Study 1 was conducted to conceptualize the main features of CWB (n = 135), and Study 2 was conducted using exploratory factor analysis to determine the validity of a four-factor measurement structure (n = 191). In Study 3, tests were completed to confirm the factor structure of the CWB (n = 533). Accordingly, we established a theory-based CWB measurement approach, and statistical analysis verified the convergent, divergent, and criterion validity of our CWB measurement model. Exploratory structural equation modeling rather than confirmatory factor analysis is recommended in discussions of CWB theory and practice in educational contexts. However, because our sample solely comprised Taiwanese teachers, our results are not generalizable to other occupations or cultures, even Eastern or Chinese-derived cultures. Implications for both theory and workplace counseling practice are presented.